A cleaner, sustainable approach for synthesising high purity silicon carbide and silicon nitride nanopowders using macadamia shell waste. (1st October 2016) - Rajarao, Ravindra; Sahajwalla, Veena
Abstract: In this paper, an innovative approach to synthesise silicon carbide (SiC) and silicon nitride (Si3 N4 ) nanopowders by using macadamia shell waste as a source of carbon is reported. Macadamia shell waste contains very low ash and about 20% fixed carbon and is an attractive source of material together with silica for synthesising high purity SiC and Si3 N4 nanomaterials based on carbothermal reduction and nitridation reactions. The size of synthesised nanoparticles was in the range of 20–100 nm. Results confirm the formation of β-SiC nanopowder, and 58% β-Si3 N4, 42% α-Si3 N4 phases in Si3 N4 nanopowder with negligible content of impurities. This sustainable and cleaner approach for synthesising high purity advanced materials like SiC and Si3 N4 nanoparticles could be a potential application for macadamia shell agricultural waste. Highlights: A novel approach to synthesise high purity nano SiC and Si3 N4 using biomass waste. Formation of β-SiC phase in SiC nanopowder with a diameter of 20–80 nm was confirmed. β-Si3 N4 and α-Si3 N4 phases in Si3 N4 nanopowder of 40–100 nm was confirmed. This cleaner, sustainable approach reduces the dependency on conventional raw materials.